A Novel Frameshift Homozygous Mutation in DHCR7 with a Known Missense Homozygous Mutation in the PROC in a 6-Year-Old Boy: A Child with Two Rare Genetic Diseases - Gumus, Evren (Journal of Pediatric Genetics, 2019)
In the present case report, we described a 6-year-old-boy with developmental delay, mental retardation, lack of speech, skin scars, and 2 to 3 toe syndactyly from healthy consanguineous Turkish parents. The whole exome sequencing (WES) analysis of this patient showed homozygous variant c.418T > C p.(Cys140Arg) in PROC gene and novel homozygous variant c.57dupC p.(Asn20Glnfs*2) in the DHCR7 gene. This finding demonstrated that WES is of great value for the diagnosis of two separate genetic disorders in a patient with multiple dysmorphic and other clinical features. It should also be kept in mind that the coexistence of two autosomal recessive diseases could be observed in highly related consanguineous marriages. The combined evaluation of clinical and laboratory data provided extremely valuable insight into the diagnosis of this unique case.
Keywords: DHCR7; PROC; novel mutation; co-occurrence; pediatrics